EDUKASI DAMPAK PENGGUNAAN COTTON BUD UNTUK MEMBERSIHKAN TELINGA DI NAGARI TALUAK TIGO SAKATO PESISIR SELATAN - Triansyah, Irwan; Aryaldy Zulkarnaini; Anita Darmayanti; Vina Tri Septiana; Melya Susanti; Jefri Henky; Khomeini, Khomeini; Sri Nani Jelmila (Nusantara Hasana Journal, 2024)
The use of cotton buds to clean ears is still widely done by the community without knowing the effects of using cotton buds. Cotton buds can cause otitis externa, cerumen prop and even perforation of the tympanic membrane. The purpose of community service is to provide education about the impact of using cotton buds to clean ears, as well as to create SOPs for cerumen props and ear hygiene. This community service consists of three steps, namely problem discovery, education on the impact of using cotton buds and creating SOPs for cotton buds and ear hygiene. The results of community service activities are in the form of problem discovery, increased knowledge and SOPs.The results of community service are that the community still does not know the correct way to clean ears, increased knowledge after providing education, as well as SOPs for cerumen props and ear hygiene. The conclusion of community service activities is increasing knowledge through education for health workers at the Taluak Tigo Sakato health center, SOPs for cerumen props, and SOPs for ear hygiene are expected to improve ear hygiene problems in the community.